Systematic Literature Review: Analysis of Financial Management Behavior of Students in Indonesia - Sukanto, Teguh (International Journal of Business, Law, and Education, 2025)
Based on the survey, the percentage of financial behavior among university students is lower than that of millennials. This is due to the low level of financial ability among university students. The goals of this study include: (1) variables that determine how economic behavior among influential students improves (2) financial behaviors among students. This research method used a systematic literature overview (SLR) in which international and national journals were published between 2018 and 2022. The majority of the research findings show that financial capacity has a positive effect on financial behavior. Financial ability is the advantage of developing students' self-efficacy so that students can make more confident decisions regarding financial management. However, improving financial behavior should not only focus on cognitive aspects, but also ensure emotion (positive attitude) and cone (stakeholder support to ensure program success). The importance of parents as a major factor in family socialization lies in their role as shapers of personality, attitudes and white financial behaviors